Preliminary results from a nationwide adult cardiology perspective for pulmonary hypertension: RegiStry on clInical outcoMe and sUrvival in pulmonaRy hypertension Groups (SIMURG) - Kaymaz, Cihangir; Mutlu, Bulent; Kucukoglu, M. Serdar; Kaya, Baris; Akdeniz, Bahri; Avci, Burcak Kilickiran; Tokgozoglu, Lale (Turkish Soc Cardiology, 2017)
Objective: The present study was designed to evaluate the characteristics of pulmonary hypertension (PH) and adult cardiology practice patterns for PH in our country. Methods: We evaluated preliminary survey data of 1501 patients with PH (females, 69%; age, 44.8 +/- 5.45) from 20 adult cardiology centers (AdCCs). Results: The average experience of AdCCs in diagnosing and treating patients with PH was 8.5 +/- 3.7 years. Pulmonary arterial hypertension (PAH) was the most frequent group (69%) followed by group 4 PH (19%), group 3 PH (8%), and combined pre- and post-capillary PH (4%). PAH associated with congenital heart disease (APAH-CHD) was the most frequent subgroup (47%) of PAH. Most of the patients' functional class (FC) at the time of diagnosis was III. The right heart catheterization (RHC) rate was 11.9 +/- 11.6 per month. Most frequently used vasoreactivity agent was intravenous adenosine (60%). All patients under targeted treatments were periodically for FC, six-minute walking test, and echo measures at 3-month intervals. AdCCs repeated RHC in case of clinical worsening (CW). The annual rate of hospitalization was 14.9 +/- 19.5. In-hospital use of intravenous iloprost reported from 16 AdCCs in CWs. Bosentan and ambrisentan, as monotreatment or combination treatment (CT), were noted in 845 and 28 patients, respectively, and inhaled iloprost, subcutaneous treprostinil, and intravenous epoprostenol were noted in 283, 30, and four patients, respectively. Bosentan was the first agent used for CT in all AdCCs and iloprost was the second. Routine use of antiaggregant, anticoagulant, and pneumococcal and influenza prophylaxis were restricted in only two AdCCs. Conclusion: Our nationwide data illustrate the current status of PH regarding clinical characteristics and practice patterns.
Keywords: pulmonary hypertension; preliminary survey data of Turkey